-3(12-6x)=7(8-2x)

Simple and best practice solution for -3(12-6x)=7(8-2x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(12-6x)=7(8-2x) equation:


Simplifying
-3(12 + -6x) = 7(8 + -2x)
(12 * -3 + -6x * -3) = 7(8 + -2x)
(-36 + 18x) = 7(8 + -2x)
-36 + 18x = (8 * 7 + -2x * 7)
-36 + 18x = (56 + -14x)

Solving
-36 + 18x = 56 + -14x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '14x' to each side of the equation.
-36 + 18x + 14x = 56 + -14x + 14x

Combine like terms: 18x + 14x = 32x
-36 + 32x = 56 + -14x + 14x

Combine like terms: -14x + 14x = 0
-36 + 32x = 56 + 0
-36 + 32x = 56

Add '36' to each side of the equation.
-36 + 36 + 32x = 56 + 36

Combine like terms: -36 + 36 = 0
0 + 32x = 56 + 36
32x = 56 + 36

Combine like terms: 56 + 36 = 92
32x = 92

Divide each side by '32'.
x = 2.875

Simplifying
x = 2.875

See similar equations:

| (-35)=c+(-18) | | 5x+13=3x-93 | | X=2-2 | | $45.00-30%= | | -3(m-7)=2m-4 | | 7x+2+2+3+8=180 | | -3x=x-20 | | 3x+5y=328 | | (-9)=b+(-13) | | 13=-6+2x | | 4u-8=5(4-u)-1 | | 13=6-2x | | A-4=(-5) | | 10y-2x=50 | | 6x+12+2x+60=90 | | -12.7+-4.4=x | | K+(-6)=4 | | -3x-3+9x+7-x=29 | | -3x-3+9x+7x-x=29 | | (6x-w)(7x+w)= | | 14z+11-5z= | | 2+(-9)=f-4 | | 2mp+3np+2mr+3nr= | | 3n-4+6n+2=6+4n+2 | | (-5)-(-8)=g+7 | | 4x+4=19-x | | (-37)=c+(-14) | | 6a-2-4a=3a+4+5a | | 0=-5n-2n-2n | | (-5)=b+(-11) | | -8x^2-8x+160=0 | | A-5=(-8) |

Equations solver categories